Barcoded solid-phase RNA capture for Spatial Transcriptomics profiling in mammalian tissue sections. Issue 11 (November 2018) - Salmén, Fredrik; Ståhl, Patrik; Mollbrink, Annelie; Navarro, José; Vickovic, Sanja; Frisén, Jonas; Lundeberg, Joakim
Abstract Spatial resolution of gene expression enables gene expression events to be pinpointed to a specific location in biological tissue. Spatially resolved gene expression in tissue sections is traditionally analyzed using immunohistochemistry (IHC) or in situ hybridization (ISH). These technologies are invaluable tools for pathologists and molecular biologists; however, their throughput is limited to the analysis of only a few genes at a time. Recent advances in RNA sequencing (RNA-seq) have made it possible to obtain unbiased high-throughput gene expression data in bulk. Spatial Transcriptomics combines the benefits of traditional spatially resolved technologies with the massive throughput of RNA-seq. Here, we present a protocol describing how to apply the Spatial Transcriptomics technology to mammalian tissue. This protocol combines histological staining and spatially resolved RNA-seq data from intact tissue sections. Once suitable tissue-specific conditions have been established, library construction and sequencing can be completed in 5–6 d. Data processing takes a few hours, with the exact timing dependent on the sequencing depth. Our method requires no special instruments and can be performed in any laboratory with access to a cryostat, microscope and next-generation sequencing. Spatial Transcriptomics combines histological staining and spatially resolved RNA-sequencing data from tissue sections. This protocol describes how to implement this method with mammalian tissue.